Equality Governance via Policy Analysis? : The Implementation of Gender Impact Assessment in the European Union and Gender-based Analysis in Canada /: The Implementation of Gender Impact Assessment in the European Union and Gender-based Analysis in Canada. ([2018]) - Sauer, Arn T
No abstract available